ChemInform Abstract: Micelle Promoted Supramolecular Carbohydrate Scaffold‐Catalyzed Multicomponent Synthesis of 1, 2‐Dihydro‐1‐aryl‐3H‐naphth[1, 2‐e][1, 3]oxazin‐3‐one and Amidoalkyl Naphthols Derivatives in Aqueous Medium. Issue 8 (1st March 2013) - Kumar, Atul; Gupta, Maneesh Kumar; Kumar, Mukesh
Abstract An eco‐friendly protocol produces the title compounds in a one‐pot manner, where ring closure takes place via ammonia elimination.